Boundedness for Multilinear Commutator on Hardy and Herz-Hardy Space - Gao Xinshan; Liu Lanzhe (Scientia Series A: Mathematical Sciences, 2025)
In this paper, the \((H_{μ}^{p}, L^{p})\) and \((HK_{α,μ}^{α,p}, K_{q}^{α,p})\) type boundedness for the multilinear commutator of certain integral operator.
Keywords: Integral operator; Multilinear commutator; Littlewood-Paley operator; Marcinkiewicz operator; Bochner-Riesz operator; BMO; Hardy space; Herz-Hardy space.